2010
DOI: 10.1099/jmm.0.018424-0
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae may be untypable by the multilocus sequence typing scheme due to a complete deletion of the fucose operon

Abstract: Haemophilus influenzae may be untypable by the multilocus sequence typing scheme due to a complete deletion of the fucose operon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…Six (M19067, M19102, M19104, M19171, M19365, and M19444) of the 46 isolates negative for both biomarker genes grouped with H. influenzae by the 16S assay. The fuculose operon, including the fucK gene, may be deleted in some H. influenzae strains (17,21). The results seen with the hpd PCR-negative isolates may have been due to deletions at that locus or to sequence variation at any of the primer or probe binding sites.…”
mentioning
confidence: 96%
“…Six (M19067, M19102, M19104, M19171, M19365, and M19444) of the 46 isolates negative for both biomarker genes grouped with H. influenzae by the 16S assay. The fuculose operon, including the fucK gene, may be deleted in some H. influenzae strains (17,21). The results seen with the hpd PCR-negative isolates may have been due to deletions at that locus or to sequence variation at any of the primer or probe binding sites.…”
mentioning
confidence: 96%
“…Two H. haemolyticus and seven H. influenzae strains were negative for both purT and hpd genes. The results seen with purT and hpd PCR-negative isolates may have been due to deletions at that locus or to sequence variation at any of the primer or probe binding sites (30,32).…”
Section: Discussionmentioning
confidence: 99%
“…The species misclassification of these strains by the original authors [28] exemplifies the difficulties associated with accurate speciation of Haemophilus spp. Other researchers [13,[15][16] have reported that certain H. influenzae isolates may lack fucK, one of the seven genes used in the H. influenzae MLST scheme [14]. The absence of this gene has historically confounded H. influenzae speciation attempts such as the probable incorrect assignment of fucK-negative H. influenzae strains as H. haemolyticus [42].…”
Section: • Phylogenomic Analysis Of Haemophilus Spp For Species Detementioning
confidence: 99%
“…The fucP gene resides within the fucose operon [13], which also encodes the multilocus sequencing typing (MLST) 'housekeeping' gene, fucK [14]. However, there is a growing body of evidence that certain H. influenzae strains lack some, or all, genes within the fucose operon [13,[15][16][17]. For example, a recent study using multilocus sequence analysis across 60 clinical Haemophilus spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation